Molecular Dynamics Study on the Structure Behavior of Cellulose II (Journal of Fiber Bioengineering and Informatics, 2020)
The conformational changes of hydroxyl groups affect the structure behavior directly, it is importantto study the structure properties of cellulose II. In order to explore them, the molecular structure wasinvestigated by using the molecular dynamics simulation at different temperature. The results indicatethat the initial model and the force field are reasonable. With the temperature raising, the standarddeviations of the glycosidic torsion angle φ of center and origin chains increase 56.56% and 38.63%respectively. Likewise, the standard deviations of torsional angle ψ of the center chains and originchains increase 32.89% and 34.91% respectively. The increase of standard deviations of these torsionalangles promote the flexibility of the hydroxyl groups and further correspond to the reduction of thehydrogen bond probability. The distance and probability of intersheet hydrogen bond O2c-Hc. . . O6c’are the shortest and largest respectively at different temperature. This is related to only one peak of thedihedral angle τ2 in the center chain, even if the peak decreases with temperature increasing. The largefluctuation of the intrachain hydrogen bond O3-H. . . O5 in probability and distance is directly related tothe glycosidic torsion angle φ rather than the dihedral angle τ3. However, the intersheet hydrogen bondO6c-Hc. . . O6o’ is very unstable and corresponds to the minimum steric hindrance for dihedral angleτ6. According to the probability, distance and angle of different hydrogen bond types, the intrasheethydrogen bond of cellulose II crystal is more stable than that intersheet and intrachain hydrogen bondsat different temperature.
Keywords: Torsional Angle; Structure Behavior; Cellulose II; Hydrogen Bond; Molecular Dynamics Simulation.